Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Belanja Modal Pemerintahan Daerah Kabupaten - Eky Ermal Muttaqin; Warsani Purnama Sari; Pandapotan Ritonga; Dinda Fadillah (Mahesa Research Center, 2021)
This study aims to determine the effect of regional own-source revenue and balance funds on capital expenditure in Langkat District Government. This type of research is quantitative with an associative approach. The type of data used is secondary data in the form of APBD reports obtained from the Regional Financial Management Agency and Langkat District. Data collection techniques with documentation and observation with data analysis techniques using multiple linear regression. The results showed that partially local revenue variables had significant effect on capital expenditure and balancing funds had a significant and significant effect on capital expenditure in Langkat District and simultaneously regional original income and balance funds had a positive and significant effect on capital expenditure in Langkat District.